REVIEW OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHs) IN SMOKED ANIMAL ORIGIN FOOD; A SERBIAN PERSPECTIVE - Jelena Vranešević; Suzana Vidaković Knežević; Brankica Kartalović; Snežana Škaljac; Nada Plavša; Krešimir Mastanjević; Nikolina Novakov (Archives of Veterinary Medicine, 2024)
This review article presents various aspects of polycyclic aromatic hydrocarbons (PAH) found in smoked animal-derived foods. The article covers PAHs and smoking methods, their levels and origins, regulatory aspects, existing knowledge gaps, as well as their impact on human health and future prospects concerning smoked animal-derived foods from the Republic of Serbia. Given our tradition and the widespread appreciation for smoked meat among consumers, producers are increasingly incorporating smoking into the production process of various animal and non-animal food products to encourage consumption diversification. Over the past ten years, our research has included smoking in traditional and industrial conditions. So far, we have examined the presence of PAHs in meat products, fish products and honey. Research on PAHs in grilled and smoked cheese is underway, after which we the results of the presence of PAH compounds in all types of smoked animal origin food will be available. Our findings revealed the presence of PAHs in the majority of studies conducted in the Republic of Serbia. Therefore, it is crucial to maintain continuous monitoring of their levels. Additionally, there is a need to develop models and implement solutions aimed at reducing PAHs in animal-derived foods intended for human consumption.